Summation of i from 1 to n of Summation of j from 1 to i
Jump to navigation
Jump to search
Theorem
- $\ds \sum_{i \mathop = 1}^n \sum_{j \mathop = 1}^i a_{i j} = \sum_{j \mathop = 1}^n \sum_{i \mathop = j}^n a_{i j}$
Proof 1
- $\ds \sum_{i \mathop = 1}^n \sum_{j \mathop = 1}^i$
can be expressed as:
- $\ds \sum_{\map R i} \sum_{\map S {i, j} } a_{i j}$
where:
- $\map R i$ is the propositional function $1 \le i \le n$
- $\map S {i, j}$ is the propositional function $1 \le j \le i$
We wish to find a propositional function $\map {S'} j$ which is to be:
- there exists an $i$ such that both $1 \le i \le n$ and $1 \le j \le i$
This is satisfied by the propositional function:
- $\map {S'} j := 1 \le j \le n$
Next we wish to find a propositional function $\map {R'} {i, j}$ which is to be:
- both $1 \le i \le n$ and $1 \le j \le i$
This is satisfied by the propositional function:
- $\map {R'} {i, j} := j \le i \le n$
Hence the result, from Exchange of Order of Summation with Dependency on Both Indices.
$\blacksquare$
Proof 2
\(\ds \sum_{i \mathop = 1}^n \sum_{j \mathop = 1}^i a_{i j}\) | \(=\) | \(\ds \sum_{i, j \mathop \in \Z} a_{i j} \left[{1 \le i \le n}\right] \left[{1 \le j \le i}\right]\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{i, j \mathop \in \Z} a_{i j} \left[{1 \le j \le i \le n}\right]\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{i, j \mathop \in \Z} a_{i j} \left[{1 \le j \le n}\right] \left[{j \le i \le n}\right]\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{j \mathop = 1}^n \sum_{i \mathop = j}^n a_{i j}\) |
$\blacksquare$
Example
Let $n = 3$.
\(\ds \sum_{i \mathop = 1}^3 \sum_{j \mathop = 1}^i a_{i j}\) | \(=\) | \(\ds \sum_{j \mathop = 1}^1 a_{1 j} + \sum_{j \mathop = 1}^2 a_{2 j} + \sum_{j \mathop = 1}^3 a_{3 j}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \left({a_{1 1} }\right) + \left({a_{2 1} + a_{2 2} }\right) + \left({a_{3 1} + a_{3 2} + a_{3 3} }\right)\) |
\(\ds \sum_{j \mathop = 1}^3 \sum_{i \mathop = j}^3 a_{i j}\) | \(=\) | \(\ds \sum_{i \mathop = 1}^3 a_{i 1} + \sum_{i \mathop = 2}^3 a_{i 2} + \sum_{i \mathop = 3}^3 a_{i 3}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \left({a_{1 1} + a_{2 1} + a_{3 1} }\right) + \left({a_{2 2} + a_{3 2} }\right) + \left({a_{3 3} }\right)\) |